Incidence of Occult Carcinoma and High-Risk Lesions in Mammaplasty Specimens - Beth C. Freedman; Sharon M. Rosenbaum Smith; Alison Estabrook; Jasminka Balderacchi; Paul I. Tartter (International Journal of Breast Cancer)
Objectives. To determine the incidence and type of premalignant or malignant changes in mammaplasty specimens and to determine the incidence of these changes according to age distribution. Methods. Retrospective database review of patients who underwent a reduction mammaplasty between 1999 and 2009 was performed from pathology records at a single institution. Results. 700 patients were identified. Of the 644 patients who had bilateral reductions, 25 (4%) had significant pathologic findings. The likelihood of finding premalignant changes or cancer increased with advancing patient age (0.8 percent for patients <40 years old and 10 percent for patients >60 years old). Of the 56 patients who underwent unilateral mammaplasty, 12 patients (21%) had significant pathologic findings. The incidence of finding premalignant changes or cancer in this population also increased with advancing patient age (0 for patients <40 years old to 25 percent for patients >60 years old). Conclusions. When a unilateral mammaplasty is performed to match a breast reconstructed after cancer surgery, the likelihood of identifying premalignant changes or cancer increases more than fourfold. Therefore, one should consider additional radiologic imaging in the preoperative workup of patients with a history of carcinoma prior to undergoing unilateral mammaplasty.